1990
DOI: 10.1104/pp.93.2.825
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase Activity in Leaves and Its Role in the First Step of C4 Photosynthesis

Abstract: In C4 plants carbonic anhydrase catalyzes the critical first step of C4 photosynthesis, the hydration of CO2 to bicarbonate. The maximum activity of this enzyme in C4 leaf extracts, measured by H production with saturating CO2 and extrapolated to 250C, was found to be 3,000 to 10,000 times the maximum photosynthesis rate for these leaves. Similar activities were found in C3 leaf extracts. However, the calculated effective activity of this enzyme at in vivo C02 concentrations was apparently just sufficient to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
148
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(156 citation statements)
references
References 10 publications
4
148
1
3
Order By: Relevance
“…The HCO 3 Ϫ that is utilized by ACCase to form malonyl-CoA is released as CO 2 by subsequent reactions of the fatty acid synthase complex. It is possible that an enzymatic hydration of CO 2 at this point increases the efficiency of CO 2 utilization in plastids, a concept that is similar to the conservation of CO 2 in mesophyll cells of C 4 plants by the cooperative action of CA and phosphoenolpyruvate carboxylase (Hatch and Burnell, 1990). In fact, CA in plastids may interact specifically with ACCase and enzymes of the fatty acid synthase complex to efficiently "channel" carbon into fatty acid (Roughan and Ohlrogge, 1996), although a direct interaction remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCO 3 Ϫ that is utilized by ACCase to form malonyl-CoA is released as CO 2 by subsequent reactions of the fatty acid synthase complex. It is possible that an enzymatic hydration of CO 2 at this point increases the efficiency of CO 2 utilization in plastids, a concept that is similar to the conservation of CO 2 in mesophyll cells of C 4 plants by the cooperative action of CA and phosphoenolpyruvate carboxylase (Hatch and Burnell, 1990). In fact, CA in plastids may interact specifically with ACCase and enzymes of the fatty acid synthase complex to efficiently "channel" carbon into fatty acid (Roughan and Ohlrogge, 1996), although a direct interaction remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Maeda et al (2000) identified a gene (CmpA) that encodes a substrate-binding protein that can specifically bind to HCO 3 Ϫ in cyanobacteria, which may further aid in the diffusion of HCO 3 Ϫ and elevation of CO 2 in the carboxysome. In C 4 plants, CA is localized to the cytosol of mesophyll cells, where it supplies HCO 3 Ϫ to phosphoenolpyruvate carboxylase (Burnell and Hatch, 1988;Hatch and Burnell, 1990), and calculations show that without CA, the rate of photosynthesis is reduced. In fact, a recent study with transgenic Flaveria bidentis clearly supported a role for CA in the assimilation of CO 2 in C 4 plants (Ludwig et al, 1998).…”
mentioning
confidence: 99%
“…The mesophyll CA is thought to play a crucial role in C4 photosynthesis by providing HCO 3 -for PEP carboxylase (Hatch & Burnell 1990). In fact, the presence of CA in C4 plants has been suggested to accelerate the rate of photosynthesis in C4 plants 10 4 -fold over what it would be if this enzyme were absent .…”
Section: Plantsmentioning
confidence: 99%
“…The abundance of CAs in plant leaves as well as their various subcellular locations suggest that CAs may play multiple roles in plant metabolism, notably fatty acid synthesis, amino acid biosynthesis, and photosynthesis (Hatch and Burnell, 1990;Badger and Price, 1994;Fett and Coleman, 1994;Raven and Newman, 1994;Hoang and Chapman, 2002). Clearly, any metabolic reaction that produces or consumes CO 2 or HCO 3 2 has the potential to be affected by CA activity.…”
mentioning
confidence: 99%
“…CA activity may play an important role in C 4 photosynthesis, as the majority of carbon fixed by phosphoenolpyruvate carboxylase (PEPC) that moves through the C 4 cycle initially passes through a CAcatalyzed reaction (Hatch and Burnell, 1990;Badger and Price, 1994). CA antisense constructs, which reduce the activity of cytosolic CA in Flaveria bidentis mesophyll cells by at least 70%, lead to diminished rates of photosynthesis, although CA levels must be severely reduced in order to see effects on photosynthesis rates, due to the high enzymatic activity of CA (von Caemmerer et al, 2004).…”
mentioning
confidence: 99%